2016
DOI: 10.1038/cdd.2016.79
|View full text |Cite
|
Sign up to set email alerts
|

The de-ubiquitylating enzyme DUBA is essential for spermatogenesis in Drosophila

Abstract: De-ubiquitylating enzymes (DUBs) reverse protein ubiquitylation and thereby control essential cellular functions. Screening for a DUB that counteracts caspase ubiquitylation to regulate cell survival, we identified the Drosophila ovarian tumour-type DUB DUBA (CG6091). DUBA physically interacts with the initiator caspase death regulator Nedd2-like caspase (Dronc) and de-ubiquitylates it, thereby contributing to efficient inhibitor of apoptosis-antagonist-induced apoptosis in the fly eye. Searching also for non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Our data also identified transcripts of the Cop9 signalosome genes, CSN5 and CSN6, with strong transcript enrichment in early stages, supporting their known function in early differentiation [ 34 ]. Duba , which has transcript accumulation in the basal region, where elongation takes place, was shown to have an important function in non-apoptotic caspase regulation during late spermatogenesis [ 35 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data also identified transcripts of the Cop9 signalosome genes, CSN5 and CSN6, with strong transcript enrichment in early stages, supporting their known function in early differentiation [ 34 ]. Duba , which has transcript accumulation in the basal region, where elongation takes place, was shown to have an important function in non-apoptotic caspase regulation during late spermatogenesis [ 35 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Metabolic enzymes on the surface of the mitochondria connect CRL3 containing E3 complexes for active degradation of cytoplasmic material during individualisation [ 62 ]. A deubiqutination enzyme, DUBA, is also necessary for individualisation and activation of caspase activity [ 35 ]. This suggests that there is an intimate connection and a fine regulation between mitochondria and the cytosol during the non-apoptotic degradation of cytoplasmic material during individualisation.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that DUBs can be regulated by allosteric regulation within large multimolecular complexes by phosphorylation, ubiquitination, sumoylation, proteolytic cleavage, and direct stress stimuli, such as reactive oxygen species [ 33 , 55 57 ]. Recently, several Drosophila DUBs were shown to be involved in regulation of apoptosis by stabilizing both anti- and proapoptotic cell death machinery proteins [ 38 , 39 , 58 , 59 ]. DUBAI deubiquitinase positively controls the stability of central anti-apoptotic E3 ligase DIAP1.…”
Section: Resultsmentioning
confidence: 99%
“…Another Drosophila DUB which is homologous to human USP36, called scny/et, functions as a direct or indirect positive regulator of DIAP1 [ 38 , 58 ]. The DUBA enzyme (also known as OTUD5), belonging to the OTU class of DUBs, possesses Dronc-controlling activity, whose catalytic activity is positively regulated by phosphorylation [ 39 ]. The present genetic study identified a proapoptotic function for the deubiquitinase DUSP31 , which is involved in the positive regulation of Dark/Dronc apoptosome components.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation